Do patients have worse outcomes in heart failure than in cancer? A primary care‐based cohort study with 10‐year follow‐up in Scotland. (3rd May 2017) - Mamas, Mamas A.; Sperrin, Matthew; Watson, Margaret C.; Coutts, Alasdair; Wilde, Katie; Burton, Christopher; Kadam, Umesh T.; Kwok, Chun Shing; Clark, Allan B.; Murchie, Peter; Buchan, Iain; Hannaford, Philip C.; et al.
Abstract: Aims: This study was designed to evaluate whether survival rates in patients with heart failure (HF) are better than those in patients with diagnoses of the four most common cancers in men and women, respectively, in a contemporary primary care cohort in the community in Scotland. Methods and results: Data were obtained from the Primary Care Clinical Informatics Unit from a database of 1.75 million people registered with 393 general practices in Scotland. Sex‐specific survival modelling was undertaken using Cox proportional hazards models, adjusted for potential confounders. A total of 56 658 subjects were eligible for inclusion in the study. These represented a total of 147 938 person‐years of follow‐up (median follow‐up: 2.04 years). In men, HF (reference group; 5‐year survival: 55.8%) had worse mortality outcomes than prostate cancer [hazard ratio (HR) 0.61, 95% confidence interval (CI) 0.57–0.65; 5‐year survival: 68.3%], and bladder cancer (HR 0.88, 95% CI 0.81–0.96; 5‐year survival: 57.3%), but better outcomes than lung cancer (HR 3.86, 95% CI 3.65–4.07; 5‐year survival: 8.4%) and colorectal cancer (HR 1.23, 95% CI 1.16–1.31; 5‐year survival: 48.9%). In women, HF (reference group; 5‐year survival: 49.5%) had worse mortality outcomes than breast cancer (HR 0.55, 95% CI 0.51–0.59; 5‐year survival 77.7%), but better outcomes than colorectal cancer (HR 1.21, 95% CI 1.13–1.29; 5‐year survival 51.5%), lung cancer (HR 3.82, 95% CI 3.60–4.05; 5‐year survival 10.4%), and ovarian cancer (HR 1.98, 95% CI 1.80–2.17; 5‐year survival 38.2%). Conclusions: Despite advances in management, HF remains as 'malignant' as some of the common cancers in both men and women.